Common Pitfalls in using Online Platforms for Data collection in COVID times and its implications - Solanki, Hariom Kumar; P, Giridara Gopal; Rath, Rama Shankar (Nepal Journal of Epidemiology, 2020)
In recent COVID-19 times conducting online research is the only feasible type of research for many authors. However, like other methods of data collection this method also bears some inherent issues linked to method of the study. The authors must understand the common pitfalls related to online data collection before planning and before interpreting the results. This letter mainly deals with the issues related to the online data collection.